The Effect of Sediment Transport For Flood Discharge Prediction Based on Awlr and River Bathymetry - Angga Yoga Pranatan; Indratmo Soekarno; Arie Setiadi Moerwanto; Eka Oktariyanto Nugroho (Syntax Corporation, 2022)
Rivers have very important benefits for the survival of the community. However, rivers can also cause problems if not managed properly, especially can cause flooding or sedimentation, one of which is the Sayung River. The Sayung River is a downstream river that empties into the north coast where sedimentation naturally occurs so that in a building plan or flood runoff on the Sayung River it is necessary to consider aspects of the planned flood discharge and sedimentation that occurs because it is something that cannot be separated. If the capacity of the river channel is not able to accommodate the flood discharge so the flood overflow causes disasters for the community. On this basis, the researchers developed a flood and sediment analysis in one frame using a quasi-unsteady flow hecras application by modifying the upstream boundary value, namely daily data for 8 years (AWLR data) to see sedimentation for 8 years and the 8th year given a bankful discharge and planned floods Q2, Q25, Q50 to determine the cross-sectional capacity of the Sayung River after sedimentation occurs, then at the downstream boundary in the form of tidal data (MSL:+ 1.30 m) because it empties into the sea. The analysis was carried out 4 times with an upstream limit of 1. use the data as is (validated with rainfall data by the sacramento method) and bankful discharge (+ 57.18 m3/s) in the 8th year, the sedimentation was + 378.977 m3and there is no embankment runoff. 2, use the baseflow and discharge data for Q2 (Â± 63.22 m3/s) in the 8th year, it is found that sedimentation of + 360.117 m3does not occur embankment runoff. 3, use baseflow and design flood discharge data for Q25 (+ 120.53 m3/s) there is embankment runoff at station + 5100 (upstream) with runoff height 8cm.4, use baseflow data and planned flood discharge Q50 (+141.31 m3/s) there was embankment runoff at station +5100 with a runoff height of + 25cm.